Preliminary study on biohydrogen production by E. coli from sago waste - Mohamad Puad, Noor Illi; Sulaiman, Sarina; Azmi, Azlin Suhaida; Shamsudin, Yusra; Mel, Maizirwan (Taylor's University, 2015)
Sago waste which has not been fully utilised is a potential substrate for biotechnological applications. This study is concerned with hydrogen gas production by Escherichia coli (E. coli) using dark fermentation and sago waste as the substrate. Glucose content after acid pre-treatment process for sago waste at 90°C for 40 minutes was 2.150 g/L. Inoculum size, pH and temperature were the 3 factors investigated during fermentation process. Design of experiment was performed using Central Composite Design (Design Expert v6.0.8). A maximum yield of 2.22 mol H2/ mol glucose was achieved from Run 8 at the pH of 6, temperature of 40°C and 30% inoculum size.